ANALISIS REDUKSI INTENSITAS CAHAYA PADA CONTACT LENSES DAN DAMPAKNYA BAGI PEMAKAI - Bhekti Kumorowati; Mahardika Prasetya Aji; Sulhadi Sulhadi; Fuad Ardani Rahman (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The analysis of light intensity reduction that pass the contact lenses and the identification of contact lenses’ ability as the eyes protector are conducted by measuring light intensity reduction after penetrate contact lenses, then decide the focus of the topic that involved the light’s ability to penetrate contact lenses, investigation from the quantum physics point of view, and analysis of physical lenses as eyes protector. The negative impact of sunlight radiation is the damage of retina tissue in the eyes. The damage of this tissue is the consequence of the bigness of wavelength; it doesn’t come from the light intensity. Thereby, the contact lenses that are not layered by anti UV can’t be protector from the damage of eyes tissue. Those contact lenses play role as polarizer that is only able to reduce the light intensity. If the light intensity that is entering the eyes decreased, as a result, it will decrease dazzled effect which causes eyesight clearer. Power of light intensity reduction from contact lenses is in line with water-content seen based on the trend of attenuation coefficient quantity. Attenuation coefficient produced by contact lenses which has 38% of water content is 0,46 and 60% of light source produce by laser pointer is 0,56, fluorescent light source is 0,34 and 0,40, and sun light is 0,41 and 0,45. Recommendation in choosing water-content in contact lenses depends on the user’s tears production. If the user’s tears production is rather in a great quantity, it is recommended to use contact lenses with high water-content in order that the position of contact lenses is not easy to shift, although the power of light intensity reduction is rather small, vice versa.Keywords:Contact Lenses, Light Intensity, Wavelength, Photoelectron.